On-and-off dynamics of a creeping frictional system - Blanc, Baptiste (2014)
We report on the dynamics of a model frictional system submitted to minute external perturbations. The system consists of a chain of sliders connected through elastic springs that rest on an incline. By introducing cyclic expansions and contractions of the rest length of the springs, we induce the reptation of the chain. Decreasing the amplitude of the perturbation below a critical value, we observe an intermittent creep regime characterized by alternated periods of reptation (flowing state) and rest (quiescent state). A further decrease of the perturbation leads to the disappearance of the reptation. The width of the transition region between the continuous creep and the full stop (i.e., the range of excitation amplitudes where the intermittent creep is observed) is shown to depend on the difference between the static (μ s ) and the dynamic (μ d ) friction coefficients. For μ s = μ d the intermittent creep is not observed. Studying the statistical features of the intermittent creep regime for any given perturbation amplitude, we find that the time the system resides in each state (flowing or quiescent) suggests that: i) reptation events are uncorrelated, and ii) rest events are history dependent. We show that this latter history dependence is consistent with the aging of the stress state inside the chain of sliders during the quiescent periods.